Gamification Elements for Application in the Brazilian Navy Simulated Training Context - Souza, Tamyres Bezerra de; Almeida, Raphael de Souza e; Raposo, Alberto Barbosa; Silva-Calpa, Greis Francy Mireya (Journal on Interactive Systems, 2026)
Although gamification presents the potential to increase engagement and motivation in learning environments, there are still gaps regarding the suitability of gamification elements for specific contexts, such as military training simulators. In this context, this study aims to identify which gamification elements are most appropriate for military training simulators, in order to contribute to the training process without compromising the fidelity of reality. This study also investigates the challenges related to the appropriation and perception of these elements in SiBART, a 3D military training simulator for combat vehicles. To achieve this objective, this research was carried out in different stages, including the identification of gamification elements in simulators according to the literature, the definition of the most attractive or relevant gamification elements according to the perception of military users, the redesign of the SiBART simulator, the use of gamified and non-gamified versions of the simulator by military personnel, with a counterbalanced order of use, and the collection of qualitative data through semi-structured interviews. The results indicate that the acceptance of gamification in the military context depends on the alignment of the proposed elements with the reality of training and with military values and practices. It was observed that gamification can contribute tactical challenges and time pressure aligned with military practice, with collaborative elements (such as gifting) that reflect companionship being well-accepted. In contrast, elements conflicting with doctrine (such as shops and individual rankings) may compromise fidelity. Finally, the perception and appropriation of gamification also depend on improvements in usability, visual integration, and system stability.